Pronunciation Difficulties and Challenges in the Field of Research in Jordan - Naser, Issa Mohammad; Hamzah, Mohammed Hilmi (Journal of Humanities & Social Sciences, 2022)
This paper presents the current evidence regarding English pronunciation challenges and problems in the Jordanian context by reviewing related literature. The present study was carried out to determine the extent to which pronunciation research regarding challenges is carried out in Jordan. The available literature on pronunciation is limited to phonological variances, consonants’ and vowels’ variations, syllable structure differences and similarities, and mother tongue as an effective element. In order to achieve this objective identifying pronunciation difficulties and challenges in the field of research in Jordan, this study followed systematic literature review (SLR) framework adapted from previous studies in this regard. The findings revealed that one of the key problems in learning English language pronunciation is related to the socio-psycho variables e.g., anxiety, self-confidence, motivation, attitudes and so on noting that studies investigated did not present these factors in detail and they focused more on the role of learners’ native language, exposure to language, phonemic variations and vowels, and syllable structures’ differences. Hence, future studies in this regard are recommended to investigate the challenges related to anxiety, self-confidence, motivation, attitudes and their role on affecting pronunciation teaching and learning.
Keywords: Pronunciation; English; EFL; Literature Review; Jordan